1995
DOI: 10.1016/0014-5793(95)00307-u
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite‐mediated oxidative protein modifications

Abstract: Proteins are targets of reactive species and detection of oxidatively modified proteins is often used as an index of oxidative stress. Peroxynitrite is a strong oxidant formed by reaction of nitric oxide with superoxide. Using fatty acid-free bovine serum albumin as a model we examined peroxynitrite-mediated protein modifications. The reaction of protein with peroxynitrite resulted in the oxidation of tryptophan and cysteine, in the nitration of tyrosine, in the formation of dityrosine, in the production of 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
305
3
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(318 citation statements)
references
References 21 publications
8
305
3
2
Order By: Relevance
“…2). In agreement with our observation of TIMP-1 fragmentation, recently Ischiropoulos and A1-Mehda have shown that ONOO-can cause partial fragmentation of fatty acid-free bovine serum albumin [25]. Evidence for the generation of ONOO-in vivo has recently been obtained by the detection of nitrotyrosine in inflammatory sites [9,21] and body fluids [8].…”
Section: Discussionsupporting
confidence: 91%
“…2). In agreement with our observation of TIMP-1 fragmentation, recently Ischiropoulos and A1-Mehda have shown that ONOO-can cause partial fragmentation of fatty acid-free bovine serum albumin [25]. Evidence for the generation of ONOO-in vivo has recently been obtained by the detection of nitrotyrosine in inflammatory sites [9,21] and body fluids [8].…”
Section: Discussionsupporting
confidence: 91%
“…OONOcan oxidize lipids, oxidize methionine and tyrosine residues in proteins and oxidizes DNA to form nitroguanine [60]. The nitrotyrosine residues are considered as marker of peroxynitrite induced cellular damage [61].…”
Section: Peroxynitrite (Oono -) and Other Reactive Nitrogen Speciesmentioning
confidence: 99%
“…Peroxynitrite has been used in many investigations, added to the test medium as previously synthesized from nitrite ions and H 2 O 2 under acidic conditions [22,23]. Physiologically it is a product of nitric oxide and superoxide [25].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis was accomplished by mixing sodium nitrite and acidified hydrogen peroxide solutions and then stopping the decomposition of the product peroxynitrous acid (ONOOH) by adding NaOH solution to convert it to basic form (ONOO 2 ) in a stop-flow tubing system. The method is widely used in the literature to determine the effect of peroxynitrite on proteins [23].…”
Section: Synthesis Of Pn (Onoo 2 )mentioning
confidence: 99%